The penalty in football - Vicente, A.; Fernando, C.; Lopes, H.; Almada, F. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The penalty is important in a football game, because of the percentage of achieved goals, and since through them the tie situations can be resolved. It is known by "the lottery`. We reject, however, these statements, because in previous studies we`ve found that, considering 8 possible directions (1 - initial position, 2 - up, 3 other - right: high, medium low and, 3 more identical to the left) for the goalkeeper to displace in order to defend the ball, in more than 40% of the situations, they`ve chosen the correct direction (even arriving late), which would not have been possible if the decision was purely random. The question we ask, to diagnose and prescribe training situations with greater intentionality, is: which variables settle the success in a penalty? METHODS We`ve analyzed 250 penalties, through image digitization of video, football games of the FIFA and UEFA top competitions over the last 10 years. Knowing the space (e) that the ball should travel to the goal (11m), the goal dimensions (2.44mx7,32m), that one second of film contains 25 frames (0,04 seconds), we measured the time the goalkeepers took to move up to intercept the ball, the time that the ball took to reach the goal or be intercepted, the moment when the goalkeeper started his displacement in relation with the kick, and the ball average speed We`ve also defined, in the situations that haven`t ended in goal, what corrections should be made into the striker to be successful. We`ve made the same analysis for the goalkeepers in situations where they could not avoid the goal. In this sense, we`ve defined what corrections should be made and when these could result in success for both the striker and the goalkeeper. After making the sequence we`ve functionally defined what was happening in each penalty. RESULTS From the 250 penalties analyzed, we`ve seen that: - 157 (62,8%) were scored; - The other 93 (37,2%) weren`t scored. From theses, 44 were intercepted by the goalkeeper (47,3%) and in the other 49 the ball was not kicked in the goal direction (52,7%). - We`ve also get that: • the goalkeepers reaction time was at least 0,7 seconds (complex reaction time) • the ball time to reach the goal even varied between 0,4 and 1,2 seconds was only higher that 0,6 seconds when the goalkeeper was already out of balance when the ball was kicked. • the goalkeepers started their displacement, in average, 0,4 seconds before the ball was kicked. • in 47% of the situations the goalkeepers moved in the ball direction. DISCUSSION Although the penalty is not a purely random situation, despite the great variability of situations and values for the different variables involved, we`ve set a time where key decisions are taken either to the goalkeeper and the striker. This is the time for the kinetic energy accumulation of the movement of different segments used in the kick. At this stage there is an inverse relationship between the acceleration time and the speed that the ball can reach.